The Five-Factor Personality Inventory: Cross-Cultural Generalizability across 13 Countries - Jolijn Hendriks, A.A.J (Array, 2003)
In the present study, we investigated the structural invariance of the Five-Factor Personality Inventory (FFPI) across a variety of cultures. Self-report data sets from 10 European and 3 non-European countries were available. These countries represent the Germanic (Belgium, England, Germany, Netherlands, USA), Romance (Italy, Spain), and Slavic branches (Croatia, Czech Republic, Slovakia) of the Indo-European languages, as well as the Semito-Hamitic (Israel) and Altaic (Hungary, Japan) language families. Each data set was subjected to principal component analysis, followed by varimax rotation and orthogonal procrustes rotation to optimal agreement with (a) the Dutch normative structure, and (b) an American large-sample structure. The scree test and the internal consistency reliabilities of the varimax-rotated components served as criteria for establishing the optimal number of factors to be retained for rotation. Parallel analysis was used as a marginal third criterion, as it indicates the absolute maximum number of factors that should be extracted. According to the scree test and the internal consistency reliabilities of the components, clear five-factor structures were found in all samples except in the smallest one (USA, N=97) ; these results fitted the ones of parallel analysis which suggested that 7-9 factors would be the absolute maximum number to be retained. Internal consistency values of the five components were generally good and high congruence coefficients were found between each sample structure and both reference structures. More than 80% of the items were equally stable within each country. Based on the results, an international FFPI reference structure is proposed. This reference structure can facilitate standardized communications about Big Five scores across research programs.